2013
DOI: 10.1002/anie.201303810
|View full text |Cite
|
Sign up to set email alerts
|

pH‐Switchable Ampholytic Supramolecular Copolymers

Abstract: β-sheet-encoded anionic and cationic dendritic peptide amphiphiles form supramolecular copolymers when self-assembled in a 1:1 feed ratio of the monomers. These ampholytic materials have been designed for on-off polymerization in response to pH triggers. The cooperative supramolecular self-assembly process is switched on at a physiologically relevant pH value and can be switched off by increasing or decreasing the pH value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
120
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 124 publications
(130 citation statements)
references
References 70 publications
(39 reference statements)
5
120
0
5
Order By: Relevance
“…[273][274][275][276][277][278][279][280][281][282][283][284][285][286][287][288] One-dimensional alternating supramolecular copolymers with a nanorod-like morphology are obtained, via a combination of attractive Coulomb interactions, hydrogen bonding, and hydrophobic shielding. [289][290][291] In pHdependent characterization experiments, it was shown that the charges in the ampholytic copolymers are screened by either protonating the carboxylate or deprotonating the ammonium groups in the side chains of the comonomers, which leads to the disassembly of the copolymers at pH 5 3.6 and pH 5 8.9. Experimental characterization of the supramolecular structures included CD spectroscopy, 13 C CP-MAS NMR, TEM, as well as multiscale molecular modeling.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[273][274][275][276][277][278][279][280][281][282][283][284][285][286][287][288] One-dimensional alternating supramolecular copolymers with a nanorod-like morphology are obtained, via a combination of attractive Coulomb interactions, hydrogen bonding, and hydrophobic shielding. [289][290][291] In pHdependent characterization experiments, it was shown that the charges in the ampholytic copolymers are screened by either protonating the carboxylate or deprotonating the ammonium groups in the side chains of the comonomers, which leads to the disassembly of the copolymers at pH 5 3.6 and pH 5 8.9. Experimental characterization of the supramolecular structures included CD spectroscopy, 13 C CP-MAS NMR, TEM, as well as multiscale molecular modeling.…”
mentioning
confidence: 99%
“…Experimental characterization of the supramolecular structures included CD spectroscopy, 13 C CP-MAS NMR, TEM, as well as multiscale molecular modeling. 289 The affinity of the comonomers was increased by incorporating a more hydrophobic leucine amino acid into the peptide chains, which lead to shifts in the apparent pK a values of the FIGURE 23 Chemical structures for the b-sheet encoded dendritic peptides using an alternating sequence of alanine or leucine with glutamic acid Ar(GXEXE) 3 and lysine Ar(GXKXK) 3 , and the pH-responsive self-assembly into ampholytic supramolecular copolymers with an alternating comonomer structure. amino acid side chains and an increased stability window for the copolymers of pH 2.0-12.0.…”
mentioning
confidence: 99%
“…This, in turn, induces the disassembly of the copolymers into the monomers, when using alanine (A) and leucine (L) containing peptides. 25 The use of aromatic phenylalanine (F) alternated with charged amino acids, does Herein we show that long phenylalanine rich dendritic peptides form nanorod--like supramolecular copolymers, that are extremely stable towards changes in pH and ionic strength. Shortening the peptide sequence via the removal of just one aromatic amino acid reduces the stability, due to reduced hydrophobic shielding of hydrogen bonding and Coulomb attractive interactions.…”
mentioning
confidence: 95%
“…32, 33 We have previously reported dendritic anionic and cationic amphiphiles encoded with β--sheet peptide motifs. 25,34 These form supramolecular alternating copolymers when mixed in a 1:1 feed ratio of the comonomers, and are able to respond to pH triggers: the self--assembly is only turned on at a neutral pH when both comonomers are charged. By protonating the anionic glutamic acid (E) comonomer at low pH, or deprotonating the cationic lysine (K) complementary comonomer at high pH, attractive Coulomb interactions are screened.…”
mentioning
confidence: 99%
See 1 more Smart Citation